Tajāribu al-Habīb Hasan Baharun Fī Ta’līmi Mahārah al-Kalām Min Manẓūr al-Naẓarriyāt al-Lughawiyyah wa al-Nafsiyyah al-Tarbawiyyah - Masnun - Masnun (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2021)
ABSTRACT This study aims to reveal Habib Hasan Baharun's experiments in developing speaking skills from the perspective of linguistic theory and educational psychology. This study uses qualitative approach with historical methods. The data of this study were obtained from interviews, observation and documentation, and were validated using data triangulation techniques. This research resulted in the findings of his experiments in developing speaking skills from the perspective of linguistic theory and educational psychology. In educational psychology theory, two theoretical schools, behaviorism theory and cognitive theory, are in accordance with his experiments. The theories of behaviorism are connectionism theory, classical conditioning theory, and the law of contiguity while the cognitive theories are generative theory, which is every human being has the ability to learn language which was originally obtained from birth. Thus in the language environment he gives full freedom to his students to carry out language activities. In linguistic theory, two streams of theory, structural theory and transformative generative theory, are in accordance with his experiments. The structural theories state